Effect of Maternal Hemogloblin on Anthropometric Measurments of Newborns - Javed, Hira; Khushdil, Arshad; Tahir, Rida; Bangash, Khursheed Ali; Khan, Masud Murad (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the effect of maternal hemoglobin on the anthropometric measurements of newborns.Study design: Prospective cross-sectional study.Place and duration of study: Neonatal and Obstetric Department of Combined Military Hospital, Quetta Pakistan, from Jan 2020 to Jun 2020.Methodology: All newborn babies born during the study period were enrolled in the study. Anthropometric measurement of the newborn such as length, weight, fronto-occipital circumference (FOC), and mid chest circumference (MCC) were recorded. Moreover, latest maternal hemoglobin level in third trimester of pregnancy was observed. Results: Of 357 patients, mean newborn weight, length, FOC, and MCC were 3032.8±409.3 grams, 48.16±4.57 cm, 35.26±3.77 cm, and 32.15±1.94 cm respectively. Anemia was observed in 164(45.9%) mothers [118/164 (72%) had mild whereas 46/164(28%) had moderate anemia]. Amongst 118 mild anemic mothers, mean newborn weight, length, FOC, and MCC were 2994.9±351.9 grams, 48.43±4.45 cm, 35.08±3.64 cm, and 32.01±1.47 cm respectively. While amongst 46 moderate anemic mothers, mean newborn weight, length, FOC, and MCC were 2726.17±347.51 grams, 47.54±3.02 cm, 34.09±1.38 cm, and 31.14±2.36 cm respectively. Mean weight (p